Perspectives: Six opportunities to improve understanding of fuel treatment longevity in historically frequent-fire forests - Radcliffe, Don C.; Bakker, Jonathan D.; Churchill, Derek J.; Van Pelt, Robert; Harvey, Brian J. (Forest ecology and management, 2025)
Fuel-reduction and restoration treatments (“treatments”) are conducted extensively in dry and historically frequent-fire forests of interior western North America (“dry forests”) to reduce potential for uncharacteristically severe wildfire. However, limited understanding of treatment longevity and long-term treatment effects creates potential for inefficient treatment maintenance and inaccurate forecasting of wildfire behavior. In this perspectives paper, we briefly summarize current understanding of long-term effects of three common treatment types (burn-only, thin-only, and thin-plus-burn) in dry forests. We then propose six opportunities for future research: evaluate treatment longevity in the context of management goals and long-term treatment effects, reference departure from un-treated conditions and progress toward desired conditions, account for natural variance of dry forests and associated statistical challenges, explore within-treatment drivers of long-term responses, increase the frequency of post-treatment sampling, and incorporate spatial heterogeneity into long-term analyses. Integrating these opportunities into long-term treatment studies and adaptive management plans can improve treatment maintenance efficiency and wildfire modelling. Ultimately, improved understanding about long-term effects of treatment and treatment longevity can support climate-adaptive management that increases dry-forest resilience to wildfire. •Limited understanding of fuel treatment longevity hinders treatment maintenance planning.•We propose six opportunities to improve understanding of fuel treatment longevity.•We visually depict short- and long-term effects of three treatment types.